Similar abilities of musicians and non-musicians to segregate voices by fundamental frequency - Deroche, Mickael L. D. (J Acoust Soc Am, 2017)
Musicians can sometimes achieve better speech recognition in noisy backgrounds than non-musicians, a phenomenon referred to as the “musician advantage effect.” In addition, musicians are known to possess a finer sense of pitch than non-musicians. The present study examined the hypothesis that the latter fact could explain the former. Four experiments measured speech reception threshold for a target voice against speech or non-speech maskers. Although differences in fundamental frequency (ΔF0s) were shown to be beneficial even when presented to opposite ears (experiment 1), the authors' attempt to maximize their use by directing the listener's attention to the target F0 led to unexpected impairments (experiment 2) and the authors' attempt to hinder their use by generating uncertainty about the competing F0s led to practically negligible effects (experiments 3 and 4). The benefits drawn from ΔF0s showed surprisingly little malleability for a cue that can be used in the complete absence of energetic masking. In half of the experiments, musicians obtained better thresholds than non-musicians, particularly in speech-on-speech conditions, but they did not reliably obtain larger ΔF0 benefits. Thus, the data do not support the hypothesis that the musician advantage effect is based on greater ability to exploit ΔF0s.